Kinetic study of bioethanol production from agroindustrial residues of ripe banana peel - Romero Bonilla, Hugo (2019)
This research addresses the application of compound polyethylene glycol (PEG) of molecular weight 1500, whose objective is to degrade the inhibiting compounds present during the enzymatic hydrolysis of Cavendish variety ripe banana peels. Likewise, three experiments were conducted on 60% ground banana peel, to which PEG was added at different concentrations: 0.01; 0.02; and 0.03 g/g biomass. The enzymatic hydrolysis was performed with conidia of the Trichoderma viride fungus and its subsequent alcoholic fermentation with commercial active dry yeast Saccharomyces cerevisiae, which was previously activated. The best result corresponds to the PEG3 experiment (0.03 g/g biomass), with which a greater increase of reducing sugars was obtained. In addition, significant differences were found (p<0.5) in the glucose obtained among the three hydrolytic treatments. The results show that bioethanol can be obtained from the lignocellulosic residues of ripe banana peel, whose 7% v/v yield obtained is close to others reported in the same field of study. Finally, the analysis of the variable costs of the pretreatment, applied to the banana peel for the production of the ethanol obtained, makes it possible to estimate that the method proposed in this article is less expensive compared to other procedures, demonstrating a higher bioethanol yield obtained in less time.